Tree-Ring Dates for the Maximum Little Ice Age Advance of Kaskawulsh Glacier, St. Elias Mountains, Canada - Reyes, Alberto V.; Luckman, Brian H.; Smith, Dan J.; Clague, John J.; Van Dorp, Richard D. (ARCTIC, 2009)
A dendroglaciological study at Kaskawulsh Glacier provides the first calendar dating of a Little Ice Age glacier advance in the northeast St. Elias Mountains of Yukon Territory. Ring series from white spruce trees, Picea glauca (Moench) Voss, that had been sheared, tilted, and killed by deposition of till at the glacier’s terminal moraine were cross-dated with a millennium-length ring-width chronology developed at a site near the south end of Kluane Lake, about 25 km north of the glacier forefield. Six cross-dated samples from two sites at Kaskawulsh Glacier suggest that the north lobe of the glacier reached its greatest Holocene extent in the mid-1750s. Additional limited data suggest that the east lobe may have reached its maximum extent somewhat earlier (ca. 1717). This chronology of Little Ice Age activity of Kaskawulsh Glacier is consistent with well-dated glacier chronologies from adjacent mountain ranges in coastal and interior Alaska. The results also demonstrate the potential to derive calendar dates from subfossil wood in the St. Elias Mountains that hitherto had been dated only with much lower precision, using radiocarbon techniques. L’étude dendroglaciologique du glacier Kaskawulsh fournit la première datation de calendrier de l’avancée glaciaire du petit âge glaciaire, dans le nord-est des montagnes St. Elias, territoire du Yukon. Les séries de cernes d’épinettes blanches, Picea glauca (Moench) Voss, qui avaient été abattues, inclinées et tuées par le dépôt de till à la moraine terminale du glacier, ont été contre-datées à l’aide d’une chronologie millénaire de largeur des cernes mise au point à un emplacement situé près du côté sud du lac Kluane, à environ 25 km au nord du front du glacier. Six échantillons contre-datés provenant de deux emplacements du glacier Kaskawulsh suggèrent que le lobe nord du glacier a atteint sa plus grande étendue holocène dans le milieu des années 1750. Par ailleurs, certaines données supplémentaires suggèrent que le lobe est pourrait avoir atteint son étendue ...